2008
DOI: 10.1017/s1138741600004443
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Reports of Peer Aggression in Preschool: its Relationship to DSM-IV Externalizing Symptoms

Abstract: Objective: to establish the prevalence and associations of peer aggression as manifested in preschool children, in community-based populations and to study links with DSM-IV externalizing diagnoses. Method: Subjects were 1,104 children, 3-to-5-year-olds attending rural and urban pre-schools classes. Teachers completed the Peer Conflict Scale (PCS) to inform about direct physical and verbal aggression, object aggression and symbolic aggression and the questionnaire on psychopathology ECI-4. Results: 6.6% (n = 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…This pattern of social behavior will trigger a reaction from others according to the perceived default, whether positive or negative. Study Domènech-Llaberia (2008) found that physical aggression is the most common, followed by verbal aggression and that aggression among peers is associated with three-year old male children.…”
Section: Introductionmentioning
confidence: 99%
“…This pattern of social behavior will trigger a reaction from others according to the perceived default, whether positive or negative. Study Domènech-Llaberia (2008) found that physical aggression is the most common, followed by verbal aggression and that aggression among peers is associated with three-year old male children.…”
Section: Introductionmentioning
confidence: 99%
“…The most prevalent forms of bullying in preschool children are verbal and physical aggressiveness, social exclusion and rumor spreading (Vlachou, 2011;Vlachou et al, 2011). The physical form is more frequent in younger ages (Domènech-Llaberia et al, 2008;Perren, 2000), since the verbal form requires more developed social, cognitive and linguistic skills, which are observed at older ages (Perren, 2000). This explains the reason why verbal aggressiveness is considered to be more sophisticated (Vlachou et al, 2011).…”
Section: Early Forms Of Aggressive Behaviourmentioning
confidence: 99%
“…Classifications that were made in literature were taken into account in this study, and a classification was made based on this framework. Based on studies conducted by Hamlett (2007), Tremblay (2012), and Domenech-Llaberia et al (2008) offensive behaviors were classified as physical attack and verbal attack. Behaviors such as hitting, pushing, choking peers, damaging goods by beating or breaking, bursting with anger and shouting, overreaction and screaming, fighting with peers, and biting were coded under the physical attack theme.…”
Section: Findings Findings On Interviews With Teachers Prior To the Pmentioning
confidence: 99%